INDONESIAN TRADE UNDER CHINA FREE TRADE AREA - Tavi Supriana (Universitas Islam Indonesia, 2011)
This paper investigates the implementation of CAFTA (China-Asean Free Trade Area) on the international trade flows across Indonesia, China and the rest of ASEAN using a gravitation model. It finds the evidence that the influence of diversion and creation effects on China are significant, while the influence of both effects on Indonesia are not significant. It also finds that the diversion effect, which leads to a decrease in society’s wealth, is greater than that of the creation effect. As a consequence, the gap across countries involved in the trade agreement is wider. Keywords: CAFTA, gravitation model, diversion effect, creation effectJEL classification numbers: F13, F14, F15